High-temperature anti-sticking agent, preparation method thereof and application of high-temperature anti-sticking agent in hot bending of automotive glass
The use of expanded graphite with silicon dioxide coating addresses glass adhesion issues in hot bending processes by enhancing hydrophilicity and expansion, ensuring high-temperature stability and yield in automobile windshield production.
Patent Information
- Application Number
- CN202411351974.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The instability of the temperature in the hot bending furnace and varying arch heights of different car models cause silicon powder anti-sticking agents to fail, leading to adhesion of automobile windshield and sunroof glasses during the hot bending process, resulting in scrap and increased production costs.
A high-temperature anti-adhesive agent comprising expanded graphite with silicon dioxide uniformly deposited on its surface, enhancing hydrophilicity and expansion performance, preventing adhesion at temperatures up to 700°C.
The agent effectively prevents glass adhesion during hot bending, maintaining yield rates and reducing production costs by ensuring easy dispersion and stability at high temperatures without affecting light transmittance.
Smart Images

Figure CN119161751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-temperature anti-adhesive agents, and in particular to a high-temperature anti-adhesive agent and a preparation method and application thereof. Background Art
[0002] As one of the important safety parts of a car, the windshield and sunroof glass have special performance requirements: moisture resistance, high temperature resistance, high pressure resistance, UV protection, infrared protection, impact resistance and high safety. At present, the preparation process of automobile windshield and sunroof glass is as follows: the original glass is trimmed, ground and cleaned according to the designed size; the A piece of glass as the outer glass is printed with black edge ink and dried, and then sintered at 600℃ for about 30 minutes. The ink is basically sintered, but the glass has not deformed. A layer of silicon powder is sprayed on one side of the printed ink, dried naturally, paired with B piece, compacted, and the paired glass is placed on a mold and hot bent at 400-700℃ for 30 minutes. The actual glass deformation temperature range is between 630-700℃. The glass is hot bent by its own gravity. After separation, it is cleaned, and then a PVB film is sandwiched between the A and B glass sheets by a laminating machine for laminating. After preliminary rolling, the laminated glass is moved into an autoclave and pressurized and kept warm at 110-130℃ to bond the two glass sheets together to obtain a finished automobile windshield. In this process, due to the instability of the temperature of the hot bending furnace, the different arch heights of different car models, and the different hot bending temperatures, the silicon powder anti-sticking agent currently used can easily cause the A and B glasses to stick together during the hot bending process, resulting in scrap, affecting the yield and increasing production costs.
[0003] A Chinese patent with publication number CN111498841B discloses a method for preparing expanded graphite and its application in the adsorption of aromatic compounds. The scheme is to obtain pre-intercalated graphite by mixing one or more low-boiling alcohols with water and then adding natural flake graphite; the pre-intercalated graphite is mixed with weak or non-polar low-boiling organic compounds and then sealed and heated in an autoclave for intercalation; after intercalation, it is cooled to room temperature and expanded by microwaves. The product FEG prepared by this scheme has obvious advantages in the adsorption of organic matter, especially aromatic compounds. (This scheme is a method for preparing expanded graphite. By infiltrating an organic solvent between the layers of graphite and heating under high pressure, the volume of the organic solvent expands to expand the distance between the graphite layers, expand the surface area, and improve the adsorption capacity. The present invention improves the hydrophilicity of the prepared expanded graphite by chemical modification to prepare an expanded graphite high-temperature anti-sticking agent with good compatibility with water.) Summary of the invention
[0004] The invention provides a high-temperature anti-adhesive agent and a preparation method thereof. The high-temperature anti-adhesive agent has good expansion performance and hydrophilicity at high temperature.
[0005] The invention also discloses the application of high temperature anti-sticking agent in hot bending of automobile glass, which can effectively prevent the adhesion of A glass and B glass during the hot bending process without affecting the light transmittance of A glass and B glass.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A high-temperature anti-sticking agent comprises expanded graphite, wherein silicon dioxide is uniformly deposited in the expanded graphite, and the mass ratio of the expanded graphite to silicon dioxide is 10-30 parts:0.4-1.8 parts.
[0008] The present invention uniformly deposits silicon dioxide on the surface of expanded graphite, which not only increases the hydrophilicity of the expanded graphite, but also the expanded graphite and silicon dioxide interact with each other to synergistically improve the expansion performance at high temperature, and has good high-temperature anti-stickiness.
[0009] The high temperature in the high temperature anti-adhesive agent refers to 400-700° C. Expanded graphite is a loose and porous worm-like substance obtained by intercalating, washing, drying and high temperature expansion of natural graphite flakes.
[0010] In one preferred embodiment, the D99 of the expanded graphite is below 8μ.
[0011] According to the timeliness of vibration grinding and the subsequent usability, the D99 of expanded graphite after vibration grinding is controlled below 8μ. If the vibration grinding is too fine, the vibration grinding time will be longer, and if it is too coarse, it will be easy to block the gun and uneven during the subsequent spraying.
[0012] Expanded graphite has a flake structure, and its volume expands more than 100 times in the particle size range of 200-800 mesh.
[0013] In one preferred embodiment, the initial expansion temperature of the expanded graphite is between 180 and 300°C.
[0014] The initial expansion temperature of the expanded graphite is calculated based on the water loss temperature of silicate and the initial melting temperature of the glass ink.
[0015] The present invention also discloses a method for preparing the high-temperature anti-adhesive agent, comprising the following preparation steps:
[0016] S1, add low boiling point alcohol and expanded graphite and disperse them evenly, shake and grind them, and then discharge the materials;
[0017] Add organic acid and deionized water to the materials in S2 and S1, stir evenly, and then slowly add water-soluble silicate solution until the pH value reaches 4-6, which is the reaction end point. Filter and wash with distilled water for several times until the washing liquid is neutral;
[0018] The filter cake obtained in S3 and S2 is baked to dehydrate the silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite and then taken out for use.
[0019] Low-boiling-point alcohols are very compatible with expanded graphite, and expanded graphite can be quickly dispersed and evenly dispersed therein. Moreover, it is easy to volatilize after synthesis, dries quickly, and can dissolve organic acids very well.
[0020] Water-soluble silicates provide silicate radicals, which react with organic acids to form insoluble silicic acid that is deposited on the surface of expanded graphite. A small amount of organic acid salt produced by the reaction of organic acids and water-soluble silicates can be dissolved in a mixture of low-boiling alcohol and water. Silicic acid is dehydrated to become silicon dioxide, which is completely adsorbed on the surface of expanded graphite.
[0021] In one preferred embodiment, the mass parts of the raw materials in the preparation method are: 10-30 parts of low-boiling alcohol, 10-30 parts of expanded graphite, 0.4-7.5 parts of organic acid, 35-430 parts of deionized water, and 2-8 parts of water-soluble silicate; preferably, 12-28 parts of low-boiling alcohol, 12-28 parts of expanded graphite, 1.0-7.0 parts of organic acid, 2.5-7.5 parts of water-soluble silicate, and 44-403 parts of deionized water; further preferably, 15-26 parts of low-boiling alcohol, 15-26 parts of expanded graphite, 1.2-6.6 parts of organic acid, 3-7 parts of water-soluble silicate, and 35-430 parts of deionized water.
[0022] If the silicate concentration is too low, the reaction time and deposition efficiency will be low, while if the concentration is too high, silicate will be produced too quickly, resulting in uneven deposition.
[0023] In one preferred embodiment, the boiling point of the organic acid is between 60-150° C.; preferably, the organic acid includes one or more of formic acid, acetic acid, trifluoroacetic acid, propionic acid and acrylic acid; further preferably, the organic acid includes one or more of formic acid, acetic acid and trifluoroacetic acid.
[0024] It is ensured that the trace amount of acid remaining on the surface of the expanded graphite without reaction can be volatilized during the silicic acid dehydration process.
[0025] In one preferred embodiment, the water-soluble silicate includes one or more of sodium silicate, potassium silicate, ammonium silicate and lithium silicate; preferably, the water-soluble silicate includes one or more of sodium silicate, potassium silicate and ammonium silicate.
[0026] In one preferred embodiment, the low boiling point alcohol has a boiling point of 60-120°C and a carbon chain of no more than 4; preferably, the low boiling point alcohol includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol and isobutanol; more preferably, the low boiling point alcohol has a boiling point of 60-100°C, is miscible with water, and includes one or more of methanol, ethanol, n-propanol and isopropanol.
[0027] The longer the carbon chain and the worse the water compatibility, the more phase separation will be formed, and the soluble silicate will be difficult to precipitate on the surface of expanded graphite.
[0028] The dispersion time in S1 is 1 to 1.5 hours.
[0029] Specifically, zirconium beads with a diameter of 0.8 to 1.0 mm are added to S1 and the mixture is shaken and ground for 24 to 30 hours. Preferably, the mass of the zirconium beads is 1.5 to 2 times the total mass of the expanded graphite and the low-boiling alcohol.
[0030] The baking temperature in S3 is 150-160°C, and the baking time is 1-1.5 hours. The baking temperature is controlled at 150-160°C, which is the temperature at which silicic acid dehydrates to form silicon dioxide. If the temperature is too high, energy consumption is high, wasteful, and the intercalants between the expanded graphite layers may decompose, affecting the expansion effect.
[0031] The present invention also discloses an application of a high-temperature anti-adhesive agent in hot bending of automobile glass. The high-temperature anti-adhesive agent is evenly mixed with water, sprayed on the glass surface of the printed ink, and dried; preferably, the high-temperature anti-adhesive agent and water are mixed at a ratio of 1:8 to 10.
[0032] The high-temperature anti-sticking agent prepared by the invention has good hydrophilicity and is easily dispersed in water. During use, it can be used after being diluted with water and shaken well.
[0033] In one preferred embodiment, in the preparation of the front windshield and sunroof glass of the automobile, the A piece of glass is printed with ink, and after the surface is dried, a layer of high-temperature anti-sticking agent is sprayed on the glass surface of the printed ink. After air drying, it is paired with the B piece and fired once to form.
[0034] The mechanism of the present invention includes the following contents:
[0035] Graphite crystal is a two-dimensional macromolecular layered structure. The C atoms in each plane are bonded by C-C covalent bonds, and the layers are bonded by weak van der Waals forces. The layered structure of graphite is very typical. Each layer is a carbon atom layer. The carbon atoms in the layer form strong covalent bonds with sp2 hybrid orbits, that is, one 2s electron and two 2p electrons are hybridized and equivalent to each other. The hybrid orbits are located on the same plane and form σ bonds with each other, while the two 2P electrons that do not participate in the hybridization are perpendicular to the plane to form π bonds. This layered structure of graphite allows certain gaps between layers. Therefore, under certain conditions, atoms (or single molecules) of certain reactants (such as acids, bases, and halogens) can enter the interlayer gaps and form interlayer compounds with the carbon network plane. This graphite with interlayer compounds is expandable graphite. The distance between carbon atom layers is far, and the bonding force between layers is weak. This structure allows intercalation substances to smoothly enter the carbon interlayer without destroying the hexagonal network structure in the carbon atom layer. Therefore, natural graphite is the best matrix material for preparing graphite intercalation compounds. Expandable graphite is a crystalline compound that uses physical or chemical methods to insert non-carbonaceous reactants into the graphite interlayer, combines with the hexagonal network plane of the carbon layer, and maintains the graphite layer structure. It not only maintains the excellent physical and chemical properties of graphite, but also presents new properties that the original graphite and intercalation substances do not have due to the interaction between the intercalation substance and the graphite layer. When the graphite with intercalation compounds encounters high temperature, the intercalation compounds will decompose and generate a thrust along the vertical axis of the graphite interlayer. This thrust is much greater than the interlayer bonding force of the graphite particles. Under the action of this thrust, the graphite interlayer is pushed open, so that the graphite particles expand highly along the vertical axis, forming worm-like expanded graphite. Expanded graphite has the characteristic of high-temperature expansion. It is used as an interlayer high-temperature anti-adhesive agent in the process of hot bending of automotive glass. It has excellent anti-adhesion effect. However, the hydroxyl content on the graphite surface is very low, and the hydrophilicity is very poor. It is difficult to disperse in water. In order to improve the hydrophilicity of expanded graphite, it is necessary to wrap water-insoluble inorganic materials on the surface of expanded graphite to improve its hydrophilicity. For automotive glass, which is mainly soda-lime glass and a trace amount of aluminum oxide, the inorganic materials that can be selected are calcium carbonate, aluminum oxide, and silicon dioxide. Calcium carbonate cannot form new chemical bonds or hydrogen bonds with the surface of expanded graphite, and has poor adhesion. It is easy to separate from expanded graphite and cannot achieve good improvement effects. In the production process of laminated glass, if the presence of aluminum oxide affects the processing conditions, such as temperature, pressure, light transmittance, etc., it may also cause the adhesion between PVB film and glass to decrease. Unstable factors in the processing process may destroy the structure of the film, thereby affecting its bonding effect with the glass. Therefore, aluminum oxide is not suitable. As the main component of glass, silicon dioxide will not produce the above-mentioned side effects. In addition, silicon dioxide can form O-Si-O chemical bonds with the hydroxyl groups on the surface to improve adhesion. When used, it is strongly dispersed in water and is not easily separated from expanded graphite.
[0036] The present invention is further explained below:
[0037] 1. The present invention selects the initial expansion temperature of the expanded graphite to be between 180 and 300°C. If the initial expansion temperature of the expanded graphite is lower than 180°C, the oven temperature fluctuates slightly during the baking process after the reaction is completed, and the initial expansion temperature will be reached, resulting in premature expansion and increased particle size, which is not conducive to subsequent spraying and affects the subsequent use effect. If the initial expansion temperature of the expanded graphite is higher than 300°C, there is little expanded graphite between 300-500°C on the market, the cost is high, and the raw material selection surface is narrow. If the initial expansion temperature exceeds 500°C, the ink begins to soften and begin to melt, and the expanded graphite has not yet begun to expand, and a good anti-sticking effect cannot be achieved.
[0038] 2. The present invention uses low-boiling alcohols with boiling points ranging from 60 to 120° C., and methanol has the lowest boiling point, exceeding 60° C. Alcohols with boiling points exceeding 120° C. have more carbon atoms and poor compatibility with water, which will form phase separation, and soluble silicates are difficult to precipitate on the surface of expanded graphite.
[0039] The high-temperature anti-adhesive agent is used to effectively prevent the glass ink on the A glass (base glass) from adhering to the B glass (cover glass) during the glass hot bending process, thereby improving the yield rate of automobile windshields.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. Good hydrophilicity and easy to disperse in water: During the use of the production line, just dilute it with water to 20%, shake it well and it can be used. It is easy to use, all diluted with water, has no VOC formula, is flame retardant and environmentally friendly.
[0042] 2. Resistant to high temperatures of 500-700°C: It will not melt during the entire process of glass hot bending, causing the two pieces of glass to stick together.
[0043] 3. Flake structure: When sprayed on the surface of the ink, the fine structures are connected to each other to easily form a relatively dense structure, which protects the glass powder in the ink underneath from melting and causes the adhesion of A and B glasses.
[0044] 4. It will expand below 500℃: The glass powder in the ink will expand before it starts to melt, changing the distance between A and B glass, further preventing adhesion caused by high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0046] Figure 1 This is the water drop angle measurement diagram of untreated expanded graphite;
[0047] Figure 2 It is a schematic diagram of water droplets on the surface after the untreated expanded graphite is made into a film;
[0048] Figure 3 It is a schematic diagram of water droplets on the surface after the treated expanded graphite is made into a film;
[0049] Figure 4 This is a schematic diagram of the sticking of the glass sheets after sintering at 630°C using silicon dioxide as a high-temperature anti-sticking agent in Example 1: one end of the glass sheets is severely stuck and the two pieces of glass cannot be separated.
[0050] Figure 5 This is a schematic diagram of the sticking after sintering at 650°C using silicon dioxide as a high-temperature anti-sticking agent in Example 1: the sticking at both ends is very serious and the two pieces of glass cannot be separated.
[0051] Figure 6 This is a schematic diagram of the sticking of the sheets after sintering at 630°C with sericite as a high-temperature anti-sticking agent in Example 2: one end of the sheets is severely stuck and the two sheets of glass cannot be separated.
[0052] Figure 7 This is a schematic diagram of the sticking of the glass sheets after sintering at 650°C with sericite as a high-temperature anti-sticking agent in Example 2: the sticking at both ends is very serious and the two pieces of glass cannot be separated.
[0053] Figure 8 This is a schematic diagram of the bonding of the sheets after sintering at 630°C using flaky aluminum oxide as a high-temperature anti-sticking agent in Example 3: the adhesion at both ends is very slight and the two sheets of glass can be separated.
[0054] Fig. 9 This is a schematic diagram of the sticking of the sheets after sintering at 650°C with flaky aluminum oxide as a high-temperature anti-sticking agent in Example 3: the sticking is very serious at both ends and the two sheets of glass cannot be separated.
[0055] Fig.10 This is a schematic diagram of the sticking after sintering at 630°C using ordinary graphite as a high-temperature anti-sticking agent in Example 4: the sticking at both ends is very slight, the two pieces of glass can be separated, but the high-temperature anti-sticking agent on the glass and ink surfaces remains after washing with water.
[0056] Fig.11 This is a schematic diagram of the sticking of ordinary graphite as a high-temperature anti-sticking agent after sintering at 650°C in Example 4: one end is linearly stuck, and the other end is slightly stuck. The two pieces of glass can be separated, but the high-temperature anti-sticking agent on the glass and ink surfaces remains after washing with water.
[0057] Fig.12This is a schematic diagram of the sticking of the flake graphite as a high-temperature anti-sticking agent after sintering at 630°C in Example 5: the sticking at both ends is very slight, the two pieces of glass can be separated, but the high-temperature anti-sticking agent on the glass and ink surfaces remains after washing with water.
[0058] Fig.13 This is a schematic diagram of the adhesion after sintering at 650°C using flake graphite as a high-temperature anti-adhesive agent in Example 5: one end is linearly adhered, and the other end is slightly adhered. The two pieces of glass can be separated, but the high-temperature anti-adhesive agent on the glass and ink surfaces remains after being washed with water.
[0059] Fig.14 This is a schematic diagram of the sticking of the expanded graphite as a high-temperature anti-sticking agent after sintering at 630°C in Example 6: the two pieces of glass can be separated without sticking, but the high-temperature anti-sticking agent on the glass and ink surfaces remains after being washed with water.
[0060] Fig.15 This is a schematic diagram of the sticking of expanded graphite as a high-temperature anti-sticking agent after sintering at 650°C in Example 6: one end is slightly stuck, the two pieces of glass can be separated, but the high-temperature anti-sticking agent on the glass and ink surfaces remains after washing with water.
[0061] Fig.16 This is a schematic diagram of the sticking of the modified expanded graphite as a high-temperature anti-sticking agent after sintering at 630°C in Example 1: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0062] Fig.17 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 650°C in Example 1: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0063] Fig.18 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 630°C in Example 2: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0064] Fig.19 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 650°C in Example 2: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0065] Fig. 20 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 630°C in Example 3: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0066] Fig.21This is a schematic diagram of the bonding process after sintering at 650°C using modified expanded graphite as a high-temperature anti-sticking agent in Example 3: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is rinsed clean with water.
[0067] Fig. 22 This is a schematic diagram of the sticking of the modified expanded graphite as a high-temperature anti-sticking agent after sintering at 630°C in Example 4: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is rinsed clean with water.
[0068] Fig.23 This is a schematic diagram of the sticking of the modified expanded graphite as a high-temperature anti-sticking agent after sintering at 650°C in Example 4: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0069] Fig.24 This is a schematic diagram of the sticking of the modified expanded graphite as a high-temperature anti-sticking agent after sintering at 630°C in Example 5: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is rinsed clean with water.
[0070] Fig.25 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 650°C in Example 5: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0071] Fig.26 This is a schematic diagram of the sticking of the modified expanded graphite as the high-temperature anti-sticking agent after sintering at 630°C in Example 6: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is washed clean with water.
[0072] Fig. 27 This is a schematic diagram of the sticking of the modified expanded graphite as a high-temperature anti-sticking agent after sintering at 650°C in Example 6: the entire plate is not sticky, the two pieces of glass can be separated, and the high-temperature anti-sticking agent on the glass and ink surfaces is rinsed clean with water. DETAILED DESCRIPTION
[0073] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0074] Dry board production:
[0075] Ink model: 1L6040-IR701A (Baifu)
[0076] Glass: 2mm float glass
[0077] Printing: 200-250 mesh polyester screen printing one layer
[0078] Surface drying: 180℃x2min
[0079] Pre-burning: 450-590℃x30min
[0080] Comparative Example 1
[0081] Table 1 Comparative Example 1 Group Allocation Ratio
[0082]
[0083]
[0084] Add distilled water to a 300g glue tank, stir, add silicon dioxide, disperse evenly, take two pieces of glass that have been printed with ink, and use a 0.8-1.0mm caliber hand spray gun to spray the dispersed silicon dioxide dispersion on the ink surface, with a spraying pressure of 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0085] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0086] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0087] Comparative Example 2
[0088] Table 2 Comparative Example 2 Group Allocation Ratio
[0089] Components Manufacturer Model Weight Distilled water self made 19 Sericite GD-4 / Chuzhou Ge Rui 1
[0090] Add distilled water to a 300g glue tank, stir, add sericite, disperse evenly, take two pieces of glass that have been printed with ink, and use a 0.8-1.0mm caliber hand spray gun to spray the dispersed sericite dispersion on the ink surface, with a spraying pressure of 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0091] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0092] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0093] Comparative Example 3
[0094] Table 3 Comparative Example 3 Group Allocation Ratio
[0095]
[0096]
[0097] Add distilled water to a 300g glue tank, stir, add flake aluminum oxide, disperse evenly, take two pieces of glass that have been printed with ink, and use a 0.8-1.0mm caliber hand spray gun to spray the dispersed flake aluminum oxide dispersion on the ink surface, with a spraying pressure of 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0098] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0099] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0100] Comparative Example 4
[0101] Table 4 Comparative Example 4 Group Allocation Ratio
[0102] Components Manufacturer Model Weight Distilled water self made 19 Ordinary graphite 2800 / Shandong Henglin 1
[0103] Add distilled water to a 300g glue tank, stir, add ordinary graphite, the graphite floats on the water surface, it is difficult to disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed ordinary graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0104] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0105] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0106] Comparative Example 5
[0107] Table 5 Comparative Example 5 Group Allocation Ratio
[0108]
[0109]
[0110] Add distilled water to a 300g glue tank, stir, add flake graphite, the graphite floats on the water surface, it is difficult to disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed flake graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0111] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0112] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0113] Comparative Example 6
[0114] Table 6 Comparative Example 6 Group Allocation Ratio
[0115] Components Manufacturer Model Weight Distilled water self made 19 Expanded Graphite EG-150 / Qingdao Yanhai 1
[0116] Add distilled water to a 300g glue can, stir, add expanded graphite, the graphite floats on the water surface, it is difficult to disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0117] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0118] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0119] Example 1
[0120] Table 7 Example 1 Group Distribution Ratio
[0121]
[0122]
[0123] Take 5 parts of sodium silicate and add it into a beaker, add 125 parts of water, stir and dissolve completely for later use.
[0124] Add methanol to a three-necked flask, stir, add expanded graphite and mix evenly, disperse at high speed for 1 hour, pour the mixture into a glass bottle dedicated for shaking, add 60 parts of 0.8-1.0mm zirconium beads, shake and grind for 24 hours, detect the particle size distribution until D99 is below 8μ, discharge the material, introduce it into a three-necked flask, stir, add 1.9 parts of formic acid and 20 parts of deionized water, stir evenly, put the dissolved sodium silicate solution into a constant pressure funnel, slowly add it dropwise to the three-necked flask, stir rapidly while adding, continue to stir the reaction after the addition is completed, measure the pH value of the mixed system, until the pH value reaches between 4 and 6 as the reaction end point, filter, wash with distilled water for many times until the pH value is 6-7, put the filter cake into a 150°C oven and bake for 1 hour to dehydrate the produced silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite, and take it out for use.
[0125] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0126] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0127] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0128] Example 2
[0129] Table 8 Implementation of 2 group allocation ratios
[0130]
[0131]
[0132] Take 4.4 parts of sodium silicate and add it into a beaker. Add 138 parts of water and stir until it is completely dissolved.
[0133] Add ethanol to a three-necked flask and stir. Add expanded graphite and mix evenly. Disperse at high speed for 1 hour. Pour the mixture into a glass bottle for shaking. Add 66 parts of zirconium beads of 0.8-1.0 mm. Shake and grind for 24 hours. Detect the particle size distribution until D99 is below 8μ. Discharge the material and introduce it into a three-necked flask and stir. Add 2.2 parts of acetic acid and 22 parts of deionized water and stir evenly. Put the dissolved sodium silicate solution into a constant pressure funnel and slowly drop it into the three-necked flask while stirring rapidly. After the addition is completed, continue to stir the reaction and measure the pH value of the mixed system until the pH value reaches between 4 and 6 as the reaction end point. Filter and wash with distilled water for several times until the pH value is 6-7. Put the filter cake into a 150°C oven and bake it for 1 hour to dehydrate the produced silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite and taken out for use.
[0134] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0135] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0136] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0137] Example 3
[0138] Table 9 Example 3 group distribution ratio
[0139] High temperature anti-stick agent Manufacturer Model Weight Expanded Graphite EG-150 / Qingdao Yanhai 18 n-Propanol Aladdin 18 Formic acid Aladdin 1.4 Potassium silicate Aladdin 4.5 Deionized water self made 168
[0140] Take 4.5 parts of potassium silicate and add it into a beaker. Add 150 parts of water and stir until it is completely dissolved.
[0141] Add n-propanol to a three-necked flask, stir, add expanded graphite and mix evenly, disperse at high speed for 1 hour, pour the mixture into a glass bottle dedicated for shaking, add 54 parts of zirconium beads of 0.8-1.0mm, shake and grind for 24 hours, detect the particle size distribution until D99 is below 8μ, discharge the material, introduce it into a three-necked flask, stir, add 1.4 parts of formic acid and 18 parts of deionized water, stir evenly, put the dissolved potassium silicate solution into a constant pressure funnel, slowly add it dropwise to the three-necked flask, stir rapidly while adding, continue to stir the reaction after the addition is completed, measure the pH value of the mixed system, until the pH value reaches between 4-6 as the reaction end point, filter, wash with distilled water for many times until the pH value is 6-7, put the filter cake into a 150℃ oven and bake for 1 hour to dehydrate the produced silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite, and take it out for use.
[0142] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0143] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0144] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0145] Example 4
[0146] Table 10 Example 4 group distribution ratio
[0147] High temperature anti-stick agent Manufacturer Model Weight Expanded Graphite EG-150 / Qingdao Yanhai 24 Isopropyl alcohol Aladdin 24 Trifluoroacetic acid Aladdin 4.3 Ammonium silicate Aladdin 4.8 Deionized water self made 184
[0148] Take 4.8 parts of ammonium silicate and add it into a beaker. Add 160 parts of water and stir until it is completely dissolved.
[0149] Add isopropanol to a three-necked flask, stir, add expanded graphite and mix evenly, disperse at high speed for 1 hour, pour the mixture into a glass bottle dedicated for shaking, add 72 parts of zirconium beads of 0.8-1.0mm, shake and grind for 24 hours, detect the particle size distribution until D99 is below 8μ, discharge, introduce into a three-necked flask, stir, add 4.3 parts of trifluoroacetic acid and 24 parts of deionized water, stir evenly, put the dissolved ammonium silicate solution into a constant pressure funnel, slowly add it dropwise to the three-necked flask, stir rapidly while adding, continue to stir the reaction after the addition is completed, measure the pH value of the mixed system, until the pH value reaches between 4-6 as the reaction end point, filter, wash with distilled water for many times until the pH value is 6-7, put the filter cake into a 150°C oven and bake for 1 hour to dehydrate the produced silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite, and take it out for use.
[0150] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0151] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0152] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0153] Example 5
[0154] Table 11 Example 5 group distribution ratio
[0155] High temperature anti-stick agent Manufacturer Model Weight Expanded Graphite EG-150 / Qingdao Yanhai 16 Ethanol Aladdin 16 Trifluoroacetic acid Aladdin 2.4 Potassium silicate Aladdin 3.2 Deionized water self made 144
[0156] Take 3.2 parts of potassium silicate and add it to a beaker. Add 128 parts of water and stir until it is completely dissolved.
[0157] Add ethanol to a three-necked flask, stir, add expanded graphite and mix evenly, disperse at high speed for 1 hour, pour the mixture into a glass bottle dedicated for shaking, add 48 parts of zirconium beads of 0.8-1.0mm, shake and grind for 24 hours, detect the particle size distribution until D99 is below 8μ, discharge, introduce into a three-necked flask, stir, add 2.4 parts of trifluoroacetic acid and 16 parts of deionized water, stir evenly, put the dissolved potassium silicate solution into a constant pressure funnel, slowly add it dropwise to the three-necked flask, stir rapidly while adding, continue to stir the reaction after the addition is completed, measure the pH value of the mixed system, until the pH value reaches between 4-6 as the reaction end point, filter, wash with distilled water for many times until the pH value is 6-7, bake the filter cake in an oven at 150°C for 1 hour, dehydrate the produced silicic acid into silicon dioxide, and completely adsorb it on the surface of the expanded graphite, and take it out for use.
[0158] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0159] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0160] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0161] Example 6
[0162] Table 12 Example 6 group distribution ratio
[0163] High temperature anti-stick agent Manufacturer Model Weight Expanded Graphite EG-150 / Qingdao Yanhai 26 Methanol Aladdin 26 Formic acid Aladdin 1.9 Ammonium silicate Aladdin 5.2 Deionized water self made 200
[0164] Take 5.2 parts of ammonium silicate and add it into a beaker. Add 174 parts of water and stir until it is completely dissolved.
[0165] Add methanol to a three-necked flask, stir, add expanded graphite and mix evenly, disperse at high speed for 1 hour, pour the mixture into a glass bottle dedicated for shaking, add 78 parts of zirconium beads of 0.8-1.0mm, shake and grind for 24 hours, detect the particle size distribution until D99 is below 8μ, discharge, introduce into a three-necked flask, stir, add 1.9 parts of formic acid and 26 parts of deionized water, stir evenly, put the dissolved ammonium silicate solution into a constant pressure funnel, slowly add it dropwise to the three-necked flask, stir rapidly while adding, continue to stir the reaction after the addition is completed, measure the pH value of the mixed system, until the pH value reaches between 4-6 as the reaction end point, filter, wash with distilled water for many times until the pH value is 6-7, put the filter cake into a 150℃ oven and bake for 1 hour to dehydrate the produced silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite, and take it out for use.
[0166] Add distilled water to a 300g glue tank, stir, add modified expanded graphite, the graphite will not float on the water surface, disperse evenly, take two pieces of glass that have been printed with ink, use a 0.8-1.0mm caliber hand spray gun to spray the dispersed modified expanded graphite dispersion on the ink surface, the spraying pressure is 1.5kg / cm 2 , keep the gun at a distance of about 25cm, spray 2 "cross" shapes, let it dry and set aside.
[0167] Cover with glass B, take a pair and place them in a muffle furnace at 400-630℃ for 30 minutes, take them out and observe the adhesion of the two pieces of glass.
[0168] Cover with glass B, take another pair and place them in a muffle furnace at 400-650℃ for 30min, take them out and observe the adhesion of the two pieces of glass.
[0169] The glasses of comparative examples 1-6 and embodiments 1-6 fired at 630°C and 650°C were observed for sticking conditions, then separated and rinsed, and the residual high-temperature anti-sticking agent on the surface of glass B was observed, and its transmittance in the visible light band was tested.
[0170] The performance test results of the high temperature anti-adhesive agents prepared in Comparative Examples 1 to 6 and Examples 1 to 6 are listed in Table 13 and Table 14. The transmittance test standard refers to GB / T 40415-2021, architectural glass safety standard GB15763.2-2005, and softening point test standard GB / T 28195-2011.
[0171] Table 13 Test results of ink performance prepared by comparative examples 1 to 6
[0172]
[0173]
[0174] Table 14 Test results of ink properties prepared in Examples 1 to 6
[0175]
[0176]
[0177] Table 15 Test results of light transmittance performance of unfired B glass
[0178]
[0179] By analyzing the ink performance after sintering of Comparative Examples 1, 2, 3 and Comparative Examples 4, 5, 6, it is found that the inorganic substances used in Comparative Examples 1, 2, 3 are highly hydrophilic, and the high-temperature anti-adhesive agent remaining on the surface after sintering at 630℃ and 650℃ is easy to wash with water, which has little effect on the transmittance of the B sheet after sintering. In Comparative Examples 1, 2, 3, 3 is a sheet structure, and the anti-adhesive effect is slightly better than that of 1 and 2. Graphite is used in Comparative Examples 4, 5, 6, which has poor hydrophilicity. The high-temperature anti-adhesive agent remaining on the surface after sintering at 630℃ and 650℃ is easy to wash with water, and the residue is large, which affects the transmittance of the B sheet after sintering. In addition, in Comparative Examples 4, 5, 6, expanded graphite is used, and the anti-adhesive effect is good after sintering at 630℃ and 650℃.
[0180] Compared with Comparative Example 6, Examples 1 to 6 use modified expanded graphite, and have good anti-sticking effect after firing at 630°C and 650°C. After the surface is treated with silicon dioxide, the hydrophilicity is greatly improved from the shape of water droplets on the surface before and after the treatment. After firing at 630°C and 650°C, it can be rinsed clean with water, and the transmittance of the fired B sheet is very small. Compared with the transmittance of the unfired B sheet glass, especially the green light range of 500-600nm and the red light range of 600-700nm, there is basically no effect. The glass fired in this way is installed on the front windshield of the car, which will not affect the reaction of the driver and passengers to the traffic light, thereby ensuring the safety of the driver and passengers.
Claims
1. A high temperature anti-sticking agent, characterized in that: The invention comprises expanded graphite, in which silicon dioxide is uniformly deposited, and the mass ratio of the expanded graphite to silicon dioxide is 10-30 parts:0.4-1.8 parts.
2. The high temperature anti-sticking agent according to claim 1, characterized in that: The D99 of the expanded graphite is below 8μ.
3. The high temperature anti-sticking agent according to claim 1, characterized in that: The initial expansion temperature of the expanded graphite is between 180 and 300°C.
4. A method for preparing the high temperature anti-sticking agent according to any one of claims 1 to 3, characterized in that The method comprises the following preparation steps: S1, add low boiling point alcohol and expanded graphite and disperse them evenly, shake and grind them, and then discharge the materials; Add organic acid and deionized water to the materials in S2 and S1, stir evenly, and then slowly add water-soluble silicate solution until the pH value reaches 4-6, which is the reaction end point. Filter and wash with distilled water for several times until the washing liquid is neutral; The filter cake obtained in S3 and S2 is baked to dehydrate the silicic acid into silicon dioxide, which is completely adsorbed on the surface of the expanded graphite and then taken out for use.
5. The method for preparing the high temperature anti-sticking agent according to claim 4, characterized in that: The weight parts of the raw materials in the preparation method are: 10 to 30 parts of low-boiling alcohol, 10 to 30 parts of expanded graphite, 0.4 to 7.5 parts of organic acid, 35 to 430 parts of deionized water, and 2 to 8 parts of water-soluble silicate; preferably, 12 to 28 parts of low-boiling alcohol, 12 to 28 parts of expanded graphite, and 1.0 to 7.0 parts of organic acid. parts, 2.5-7.5 parts of water-soluble silicate, 44-403 parts of deionized water; more preferably, 15-26 parts of low-boiling alcohol, 15-26 parts of expanded graphite, 1.2-6.6 parts of organic acid, 3-7 parts of water-soluble silicate, and 35-430 parts of deionized water.
6. The method for preparing the high temperature anti-sticking agent according to claim 4, characterized in that: The boiling point of the organic acid is between 60-150° C.; preferably, the organic acid comprises one or more of formic acid, acetic acid, trifluoroacetic acid, propionic acid and acrylic acid; Further preferably, the organic acid comprises one or more of formic acid, acetic acid and trifluoroacetic acid.
7. The method for preparing the high temperature anti-sticking agent according to claim 4, characterized in that: The water-soluble silicate includes one or more of sodium silicate, potassium silicate, ammonium silicate and lithium silicate; preferably, the water-soluble silicate includes one or more of sodium silicate, potassium silicate and ammonium silicate.
8. The method for preparing the high temperature anti-sticking agent according to claim 4, characterized in that: The low boiling point alcohol has a boiling point of 60 to 120°C and a carbon chain of no more than 4; preferably, the low boiling point alcohol includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol and isobutanol; more preferably, the low boiling point alcohol has a boiling point of 60 to 100°C, is miscible with water, and includes one or more of methanol, ethanol, n-propanol and isopropanol.
9. Use of the high-temperature anti-adhesive agent according to any one of claims 1 to 3 or the high-temperature anti-adhesive agent prepared by the preparation method according to any one of claims 4 to 8 in hot bending of automobile glass, characterized in that: The high-temperature anti-sticking agent is mixed evenly with water, sprayed on the glass surface of the printing ink, and dried; preferably, the high-temperature anti-sticking agent is mixed with water at a ratio of 1:8-10.
10. Application of the high temperature anti-adhesive agent according to claim 9 in hot bending of automobile glass, characterized in that: In the preparation of the front windshield and sunroof glass of the automobile, the A piece of glass is printed with ink, and after the surface is dried, a layer of high-temperature anti-sticking agent is sprayed on the glass surface of the printed ink. After air drying, it is paired with the B piece and fired once to form.
Citation Information
Patent Citations
Preparation method of silicon carbon composite negative electrode material by taking silica sol as silicon source
CN107394121A
Preparation methods of SiO2 nano particle modified expandable graphite and flame retardant polypropylene
CN108410066A
Curved glass with patterned concave surface, manufacturing method thereof, and automobile skylight
CN110563345A
Graphene nano silicon dioxide composite material and in-situ preparation method thereof
CN114957800A
Hard alloy sintering anti-sticking coating as well as preparation method and application thereof
CN118206888A
